OER interoperability educational design: enabling research-informed improvement of public repositories - Romero-Ariza, Marta; Abril Gallego, Ana M.; Quesada Armenteros, Antonio; Rodríguez Ortega, Pilar Gema (Frontiers in Education, 2023)
According to UNESCO, open educational resources (OERs) could be tools for meeting Objective for Sustainable Development 4, as long as they have the appropriate characteristics and sufficient quality to promote citizen education. This work presents a quality analysis of OERs in a public repository using mixed methods techniques and a participatory approach. Though the quantitative results show high mean values in all the dimensions, the qualitative analysis provides a better understanding of how key stakeholders perceive particular aspects and how we can take a step forward to enhance usability and improve OER psycho-pedagogical and didactic design. The triangulation of information from different sources strengthens consistency and reliability and provides a richer perspective to inform future work.